TREE TRUNK VOLUME OF Shorea SPECIES CASE STUDY IN DARMAGA AND HAURBENTES RESEARCH FOREST IN WEST JAVA INDONESIA - Mindawati, Nina; Hendromono, Hendromono; Hiratsuka, M.; Toma, T.; Morikawa, Y.; Gintings, A. Ngaloken (Indonesian Journal of Forestry Research, 2004)
Activities of  forest management  require a well planned, systematic and well directed handling, so that  achieving  maximal  and  beneficial  results in terms  of  economic,  ecological  and  social prospects.   In relevant  to data on trunk  volume of  available tree stands  are required  to set up a plan  intended  to produce  sustainable   timber. The  research was conducted  in the Darmaga  and Haurbentes  research forests of  the Forest  and Nature  Conservation  Research and Development Center located in West Java. The  trunk  volume model as conceived  was based  on the Smalians formula employed to particular tree species (i.e.  Shorea balanggeran;  S. guisso;S.leprosula; S.  mecistopteryx; S.ovalis; S. palembanica;S. pinanga;S.  selanica;S.seminisand S.  stenoptera).This  model could estimate the trunk  volume with non-destructive    sampling.  In this way, therefore,  the trunk  volume  can be estimated  from the tree diameter  on a single variable.